If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(x) + log(x + 4) = log(12) Multiply glo * x glox + log(x + 4) = log(12) Reorder the terms: glox + glo(4 + x) = log(12) glox + (4 * glo + x * glo) = log(12) glox + (4glo + glox) = log(12) Reorder the terms: 4glo + glox + glox = log(12) Combine like terms: glox + glox = 2glox 4glo + 2glox = log(12) Reorder the terms for easier multiplication: 4glo + 2glox = 12glo Solving 4glo + 2glox = 12glo Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-12glo' to each side of the equation. 4glo + -12glo + 2glox = 12glo + -12glo Combine like terms: 4glo + -12glo = -8glo -8glo + 2glox = 12glo + -12glo Combine like terms: 12glo + -12glo = 0 -8glo + 2glox = 0 Factor out the Greatest Common Factor (GCF), '2glo'. 2glo(-4 + x) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-4 + x)' equal to zero and attempt to solve: Simplifying -4 + x = 0 Solving -4 + x = 0 Move all terms containing g to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + x = 0 + 4 x = 0 + 4 Combine like terms: 0 + 4 = 4 x = 4 Add '-1x' to each side of the equation. x + -1x = 4 + -1x Combine like terms: x + -1x = 0 0 = 4 + -1x Simplifying 0 = 4 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3a+8-7a+10=38 | | F(x)=1/3x-4 | | 5m+23=38 | | 9b-12=69 | | -x+4(x-5)=-2(-2-x)+5 | | 2h-9/3=3 | | 8a-9=87 | | X*20=57 | | 15+5m=45 | | x^2-2x=26 | | 25x+45=-65 | | x+2=x*3 | | 10-23x=17 | | 7t-7=35 | | -2x-4(x+1)=5x+9 | | -2(3x+4)-x+6=-5x-2 | | 2(x+3)=(x-3) | | 23x-10=17 | | 8=4-2x | | 153.92/4 | | 2+p=9 | | 32-3x=12+7x | | 22+11=4x-7 | | 2x+33=63 | | 9.25x+1=10x+1 | | 0=x(2x-3)(4x+1) | | 5x+4=13+2x | | x/9-8=-5 | | 0.3x^2-48x+24=0 | | 58x=870 | | 9.25x=10x | | 2(3x+4)+8=-5x-4+9 |